PENYULUHAN DAN PENCEGAHAN PENYAKIT DIARE MELALUI KEGIATAN DEMONSTRASI 6 LANGKAH MENCUCI TANGAN YANG BENAR PADA ANAK REMAJA DI PANTI ASUHAN AL HUSNA BANDAR LAMPUNG - Febria Listina; Dwi Yulia Maritasari; ASPAWI, ASRIL; Fadila Khairunnisa; Frista Dian H; Muhammad Ali S; Nabillah Dwi A; Natalia Putri; Revi Meriska W; Rima Cindi Yanti; Fajar Prasetyo R; Firdaus Dwi Prianda (Fakultas Pertanian, 2024)
Diarrhea is a major health problem for school-aged children, especially in developing countries like Indonesia. Based on data from WHO and the Ministry of Health, diarrhea is the main cause of death in children under five, with a high prevalence due to poor sanitation and open defecation habits. At the Al Husna Orphanage, diarrhea is a major concern, so health education is carried out to increase understanding of the causes, symptoms and prevention. Through interactive methods and materials in the form of presentations, discussions, and media such as leaflets and posters, this activity succeeded in increasing teenagers' knowledge about diarrhea and the importance of hygiene, especially washing hands properly. In conclusion, this counseling is effective in increasing insight and reducing the risk of spreading diarrhea in the orphanage environment.